ADVANTAGES OF CLOSED WATER SUPPLY SYSTEMS OF INDUSTRIAL ENTERPRISES - Sabirova, Dildora; Ibragimova , Aziza; Mavlanova, Yulduz (Innovative Development in Educational Activities, 2023)
Closed water supply systems today are the only rational solution to the problem of water use in industry. The use of closed water circulation systems in the design of enterprises makes it possible to locate these facilities in areas with limited water resources, but with favorable economic and geographical conditions. This engineering and environmental direction is the most progressive and promising, allowing you to simultaneously solve the problems of water supply and environmental protection.